Rehabilitation Following ACL Repair with Internal Brace Ligament Augmentation in Female Gymnast: A Resident’s Case Report - Colten Haack; Giorgio Zeppieri; Micheal W Moser (International Journal of Sports Physical Therapy)
# Introduction